Analysis of Copyright Controversies in the Music Industry Under the Fatwa of the Indonesian Council of Ulama No. 1/2003 - Damayanti Damayanti; Safwan Safwan (Hikmah, 2026)
The rapid development of digital technology and the increasing use of musical works for commercial purposes further underscore the urgency of regulating copyright and royalty systems in Indonesia. This study aims to examine the protection of music copyright based on the Indonesian Ulama Council Fatwa No. 1 of 2003 and its relationship with positive law, specifically Law No. 28 of 2014 and Minister of Law Regulation No. 27 of 2025. The study employs a descriptive qualitative method with a normative approach, supported by case studies and literature reviews to understand implementation in practice. The findings indicate that, from the Indonesian Ulama Council perspective, copyright falls under the category of huquq maliyyah (property rights), which possess economic value and must be protected. Therefore, infringements particularly those of a commercial nature without authorization e viewed as contrary to the principle of justice in Islam. Meanwhile, in positive law, copyright protection is strengthened through the role of institutions such as the National Collective Management Organization in managing and distributing royalties more systematically. Practically, this study underscores the importance of harmonizing Sharia principles with national regulations through increased transparency in royalty distribution, optimization of the performance of relevant institutions, and strengthening legal awareness among music industry stakeholders to create a fair and sustainable system in the digital age.